The impact of leadership on the professional development of teachers in complementary schools. (October 2020) - Souza, Ana; Arthur, Linet
Leadership in complementary schools is an under-researched area. This article aims to address this gap in the literature by reporting on a study which focused on Brazilian complementary schools in the United Kingdom. Distributed leadership was initially adopted as a theoretical framework to analyse the relationship between leadership style and professional development provision. The data were collected via an online questionnaire and individual semi-structured interviews with leaders, as well as focus group interviews with teachers and teaching assistants. We report here on one of the schools and argue that the contextual constraints in which it operates led to high levels of collaboration between leaders, teachers and teaching assistants. Consequently, a Community of Practice (CoP) has developed. We discuss the benefits this CoP brings to the school and suggest that conscious efforts be made to cultivate this social unit of learning to ensure the professional development of teachers in complementary schools.